MENINGKATKAN KEMAMPUAN KOMPUTASI SISWA DENGAN MODEL PEMBELAJARAN BERBASIS STEAM-PJBL - Hafild, M. Nazali Romadhon; Abdurahman; Dwi Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aims of this research to develop and implement a STEAM-PjBL based Learner Worksheet (LKPD) to improve students' computational thinking skills in class IV SDN 4 Talang. In the context of the Merdeka Curriculum, teachers have the freedom to design innovative and contextualized learning. However, the use of LKPD or interactive media has not been widely implemented in several schools in Bandar Lampung. This research is based on the view that concrete and interactive learning media can increase student creativity more effectively than conventional methods. Data from the Ministry of Education and Culture's School Report Card shows a decline in the literacy and numeracy skills of students at SDN 4 Talang in the last three years. The implementation of STEAM-PjBL is expected to overcome this problem by providing more meaningful and problem-solving-based learning. Analysis of previous research results shows that the STEAM-PjBL learning model can improve learning outcomes and students' creative thinking skills. This research uses an experimental approach by comparing learning outcomes between experimental classes that use STEAM-PjBL-based LKPD and control classes that use conventional learning methods and the research method used is 4D model development research. The results of the study are expected to contribute to improving the quality of learning in schools